CORRESPONDENTS OF RADVILA FAMILY IN THE FIRST HALF OF the 18TH CENTURY - URBAITYTĖ, RITA (Knygotyra, 2015)
The purpose of this research is to identify and present the correspondents of one influential Lithuanian family of high nobles Radvilas: O. Radvilienė (1676–1746), the widow of a vice-chancellor of the Grand Duchy of Lithuania, and two of her sons, grand hetman of Lithuania, Vilnius voivode, Vilnius and Trakai castellan M. K. Radvila “Žuvelė” [“Little Fish”] (1702–1762) and royal deputy cupbearer, grand standard bearer J. F. Radvila (1715–1760). It is a presentation of the origin, education, family, financial position, relations with nobles and among the correspondents. According to the letters stored in the Central Archives of Historical Records in Warsaw and historiography, sixteen persons who had sent news of public character and newspapers (manuscript and printed) in the first half of the 18th century to the Radvilas family are identified. We began to create a collective biography of this group, but we don’t discount the possibility of expanding it in the future. These people came from undistinguished and unknown families, but were well-educated persons of citified origin and through personal faculty, head, artfulness, luck, profitable and gainful contacts reached quite high positions. Some of them originated from small Lithuanian nobility which were career-interrelated with the Radvilas estate. They all new foreign languages, geography, were well oriented in the political situation, understood the demands of the high nobles. The majority of the correspondents worked simultaneously for several high nobles, bishops, leaders of the biggest cities, so it is possible to talk about the formation of a new occupational group in the 3rd–4th decades of the 18th century in the Polish–Lithuanian commonwealth. Members of this unofficial group were engaged in collecting and redacting news, subscribing and sending newspapers from country and abroad for remuneration, communicated, rivaled, kept in touch with each other or at least knew about one another. The main places of the concentration of correspondents were the best points of communication and spread of news – post offices and chancellery of the state. Expanding the post network required more and more service personnel in the first half of the 18th century. For the chiefs and secretaries of the Warsaw post office, work in the field of information transfer (collecting news, redacting the manuscript newspapers and newssheets, taking care of regular communication) became the main trade, so these people can be called real correspondents. These who not only sent news, but also pursued different prescriptions of the Radvilas and dealt with business, balanced between client and correspondent functions. It was impossible to survive only on the correspondent work, so even the post office personnel had extra sources of income, especially in province. For the latter and for the personnel of the state chancellery (registry and royal secretary), long-lasting contacts with the high nobles such as the Radvilas was a testimony of trust in them. This could (but also could not) provide both financial and immaterial profit.